Recent advances in carbon dioxide based copolymers. (September 2015) - Qin, Yusheng; Sheng, Xingfeng; Liu, Shunjie; Ren, Guanjie; Wang, Xianhong; Wang, Fosong
Abstract: Carbon dioxide is becoming increasingly important synthetic feedstock for chemicals and materials, since it is abundant, low-cost, non-toxic. One growing area in CO2 chemistry utilization is the development of catalysts for the polymerization of CO2 and epoxides to prepare CO2 based copolymers, including high molecular weight aliphatic polycarbonates and low molecular weight poly(carbonate-ether) polyols. Among all the aliphatic polycarbonates, poly(propylene carbonate) (PPC) has the best opportunity for scale-up commercialization. PPC is not only cheap since it contains over 40 wt% CO2, but it also exhibits good biodegradability, which has wide application in throw-away packaging materials, or even gas barrier films. Poly(carbonate-ether) polyols are low-molecular weight polyether carbonates with terminating hydroxyl groups, which are potential large scale raw materials in polyurethane industry. Herein, the recent progress of the CO2 based polymers will be highlighted, and the future in this area will be discussed.